2021
DOI: 10.1155/2021/4836933
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Development of Fintech-Served Real Economy Based on Fintech Improvement

Abstract: The new generation of information technology (IT) promotes the integration of fintech with the real economy. Existing studies emphasize the relationship between fintech and the real economy over the development level of fintech-served real economy (FtRE). To fill up the gap, this paper explores the evaluation of FtRE based on fintech improvement (FtI). Firstly, an evaluation index system (EIS) was established for fintech service efficiency (FtSE), and FtSE was measured through data envelopment analysis (DEA). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…A new economic form is introduced to the actual economy by FinTech, which is renowned for its enormous development potential and high computing power. The real economy must change and expand, and one of the main forces behind real economic growth is the development of FinTech [8], [43], [44], [63], [80].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A new economic form is introduced to the actual economy by FinTech, which is renowned for its enormous development potential and high computing power. The real economy must change and expand, and one of the main forces behind real economic growth is the development of FinTech [8], [43], [44], [63], [80].…”
Section: Resultsmentioning
confidence: 99%
“…As a result, maintaining financial stability depends on the health of the banking industry. The transfer of economic resources, liquidation and payment, financing and equity refining, risk management, information providing, and incentive provision are only a few of the fundamental duties performed by financial systems [7], [8]. The banking system is an essential component of contemporary finance and a critical area of study for ensuring the smooth operation of the financial system.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, regarding the DIFSE, Zhou and Zheng (2021) used the DEA method to assess the efficiency of fintech serving China’s real economy and found that the real economic growth, the level of urbanization, and the degree of openness were the significant factors affecting this efficiency [ 33 ]. Chen and Wang (2022) evaluated the financing efficiency of China’s strategic emerging industries using the DEA method, and confirmed that the asset–liability ratio, financial expenses, cash ratio and financing efficiency were negatively correlated, while the net asset income was a positively affecting factor [ 34 ].…”
Section: Literature Reviewmentioning
confidence: 99%